Flow Cytometry-Assessed PD1/PDL1 Status in Tumor-Infiltrating Lymphocytes: A Link With the Prognosis of Diffuse Large B-Cell Lymphoma - Chen, Zihang; Deng, Xueqin; Ye, Yunxia; Zhang, Wenyan; Liu, Weiping; Zhao, Sha (Frontiers in Oncology, 2021)
The PD1/PDL1 status of tumor-infiltrating lymphocytes (TILs) in diffuse large B-cell lymphoma (DLBCL) reflects the prognostic value and is essential for applying immunotherapy. However, the reported methods for evaluating such status were complex that may not be wild-used in clinical practice. Besides, healthy controls were not introduced for making the cut-off when evaluated the prognostic value. Therefore, this study retrospectively evaluated the PD1/PDL1 status in TILs of 24 DLBCL tissue samples and normal immune cells in 61 demographic matched healthy controls [reactive hyperplasia (RH) samples] by flow cytometry (FCM) to further investigate the prognostic value of PD1/PDL1 status in TILs by precisely determining the cut-off values and to assess the reliability of FCM. The mean fluorescence intensity (MFI) of PD1 in TIL-T-cells (median, 110) and CD8+TIL-T-cells (median, 64) were significantly higher than that of CD3+T-cells (median, 64) and CD8+T-cells (median, 34) in RH. The cut-offs of PD1/PDL1 status for analyzing prognostic values were defined considering PD1/PDL1 status of both DLBCL cases and healthy controls. High MFI of PD1 in TIL-Ts (MFI > 108, P = 0.022), high proportion of PD1+CD4+TIL-Ts (>1.1% of CD4+TIL-Ts, P = 0.049), high proportion of PD1+CD8+TIL-Ts (>2% of CD8+TIL-Ts, P = 0.025), and high MFI of PDL1 in TIL-Ts (MFI > 83, P = 0.023) were risk factors indicating inferior prognosis of DLBCL. The consistent results with previous studies using in situ detection methods proved flow cytometry a reliable method in evaluating the immune-checkpoint status of TILs which may be extensively used in clinical practice.